1999
DOI: 10.1016/s0166-1280(98)00511-9
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the adsorption of methanol on the (110) surface of γ -alumina

Abstract: The adsorption of methanol on the (110) surface of g -alumina was investigated using both ab initio and density functional theory quantum chemical methods. A [Al 3 O 9 H 10 ] ϩ cluster model comprising one tetrahedral and two octahedral aluminum cations were used to describe the surface and the mechanism of adsorption of methanol. This has allowed us to rationalize the stable structures of adsorbate and the mode of bonding. The IR frequency shifts between the gas phase and the adsorbed species were also calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Apparently, indium species exists in two valence states (oxidized and reduced) and is likely that each indium state affects the surface reactivity in a different way. Indium oxide has a less pronounced Lewis acid character than that of aluminum oxide; see ref and references therein. Therefore, increasing surface Al 2 O 3 amount may be related to the increase of the overall catalyst acidity, and vice versa for indium oxide.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Apparently, indium species exists in two valence states (oxidized and reduced) and is likely that each indium state affects the surface reactivity in a different way. Indium oxide has a less pronounced Lewis acid character than that of aluminum oxide; see ref and references therein. Therefore, increasing surface Al 2 O 3 amount may be related to the increase of the overall catalyst acidity, and vice versa for indium oxide.…”
Section: Results and Discussionmentioning
confidence: 99%
“…29,30 Their results showed that both molecular and dissociative H 2 O adsorption are obtained on a-Al 2 O 3 (0001) and that the hydroxylated alumina surface is formed exothermically. Quantum chemical calculations were performed to investigate the interaction between g-Al 2 O 3 and small molecules such as H 2 , 31 H 2 O, [30][31][32][33] H 2 S, 31,33 HCl, 34 CO, 35,36 CH 3 OH, 37 MoS 2 38 and pyridine. 32 To the best of our knowledge, the mechanisms of the H 2 O-g-Al 2 O 3 (110) interactions have not been adequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…10 DeVore and co-workers used temperature programmed desorption-FTIR to develop schematic structures for how methanol can bond to model surfaces of g-alumina. 11 The experimental studies have been supplemen-ted by theoretical investigations on alumina 12 and comparable substrates. [13][14][15] The interaction of methanol with alumina is also important in the industrial scale manufacture of methyl chloride, where methanol and hydrogen chloride are combined over high surface area alumina catalysts, e.g.…”
Section: Introductionmentioning
confidence: 99%